Targeting Aging Skin with GABALAGEN®: A Synergistic Marine Nutricosmetic Ingredient Validated Through Human Randomized Trials - Jimin Hyun; Kyoung-Min Rheu; Bae-Jin Lee; Bomi Ryu (Antioxidants)
This study introduces GABALAGEN® (GBL), a marine-derived ingredient combining low-molecular-weight fish collagen and gamma-aminobutyric acid (GABA) produced via lactobacillus fermentation. GBL contains approximately 10% GABA, making up 39% of its free amino acid profile. A 12-week, randomized, double-blind, placebo-controlled trial with 100 adults (aged 35–60) assessed its effects on aging skin. Participants consumed 1500 mg/day of GBL in jelly form, with 94% completing the study. By Week 12, the GBL group showed a 20% increase in skin hydration and a 15% reduction in wrinkle depth. Improvements in skin density and elasticity were also observed, with no adverse effects reported. In vitro tests demonstrated strong antioxidant and anti-inflammatory effects, including enhanced superoxide dismutase activity and reduced pro-inflammatory cytokine expression in UVB-irradiated keratinocytes. GBL exemplifies sustainable innovation by upcycling fishery byproducts into high-value materials while addressing stability issues common to seafood-derived products. The fermentation process ensures safety and enhances GABA’s antioxidant activity and bioavailability. This scalable method aligns with circular economic principles and global sustainability goals, extending GBL’s potential to other functional materials which were proved their safety. GBL represents a breakthrough in nutricosmetics, combining efficacy, environmental sustainability, and industrial innovation.